2021
DOI: 10.3233/jad-201014
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in the 3xTg-AD Mouse Model and Its Impact on Pre-Clinical Research

Abstract: Female sex is a leading risk factor for developing Alzheimer’s disease (AD). Sexual dimorphism in AD is gaining attention as clinical data show that women are not only more likely to develop AD but also to experience worse pathology and faster cognitive decline. Pre-clinical AD research in animal models often neglects to address sexual dimorphism in evaluation of behavioral or molecular characteristics and outcomes. This can compromise its translation to a clinical setting. The triple-transgenic AD mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 111 publications
4
33
0
Order By: Relevance
“…Clinical studies were the first to emphasize the importance of sex-divergent patterns in AD incidence, presentation, and treatment response as critical to the mechanistic etiology of dementia. Women are disproportionately diagnosed with AD [140] and are shown to carry greater pathological burdens [141]; phenotype severity is often greater in female AD mice, including the 3xTg strain used in the current study [79,82,139,142]. In the current study, we observed notable sex differences in PERG that may be supported by sex-specific vulnerability of specific RGC populations.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Clinical studies were the first to emphasize the importance of sex-divergent patterns in AD incidence, presentation, and treatment response as critical to the mechanistic etiology of dementia. Women are disproportionately diagnosed with AD [140] and are shown to carry greater pathological burdens [141]; phenotype severity is often greater in female AD mice, including the 3xTg strain used in the current study [79,82,139,142]. In the current study, we observed notable sex differences in PERG that may be supported by sex-specific vulnerability of specific RGC populations.…”
Section: Discussionmentioning
confidence: 50%
“…The relevance of this study's sex-divergent findings on retinal function in 3xTg mice must be emphasized in light of an increasing body of research identifying sex differences in disease mechanisms among animal models of AD [139]. Clinical studies were the first to emphasize the importance of sex-divergent patterns in AD incidence, presentation, and treatment response as critical to the mechanistic etiology of dementia.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the lack of NFTs in Tau-P301L female mice in those regions can be also related to the lack of motor deficits. Sex dimorphism is observed in other transgenic mouse models, but the results are contradictory [ 50 ]. Therefore, more experiments are needed in order to understand these sex-related differences more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous 3xTg mice bought from Jackson Laboratory (CA, USA) were used in this study. Since previous findings suggested that male 3xTg mice may not exhibit AD-like pathology 39 , only female mice were used in our study. In 3xTg mice, celastrol was given daily from 6 months of age till the mice reached 15 months of age with concentrations of 1 and 2 mg/kg/day ( n = 8 per group).…”
Section: Methodsmentioning
confidence: 99%